1993
DOI: 10.1086/418170
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation as a Defense Against Pathogens Transported by Sperm

Abstract: Sperm are vectors of disease. During mammalian insemination bacteria from the male and female genitalia regularly cling to sperm tails and are transported to the uterus. I propose that menstruation functions to protect the uterus and oviducts from colonization by pathogens. Menstrual blood exerts mechanical pressure on uterine tissue, forcing it to shed, and delivers large numbers of immune cells throughout the uterine cavity, directly combating pathogens. The mechanisms of menstruation show evidence of adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 207 publications
0
60
0
3
Order By: Relevance
“…These findings have potential implications for the debate concerning the evolution of menstruation. Specifically, Profet (1993) argued that menstruation evolved to rid the vaginal tract of pathogens. This idea has been largely discounted in favor of the notion that sloughing endometrial tissue may require less energy than constant uterine readiness, and evidence for elevated pathogens in the uterus before menstruation is lacking (Strassmann, 1996).…”
Section: Factors Affecting Vaginal Microbial Ecologiesmentioning
confidence: 99%
“…These findings have potential implications for the debate concerning the evolution of menstruation. Specifically, Profet (1993) argued that menstruation evolved to rid the vaginal tract of pathogens. This idea has been largely discounted in favor of the notion that sloughing endometrial tissue may require less energy than constant uterine readiness, and evidence for elevated pathogens in the uterus before menstruation is lacking (Strassmann, 1996).…”
Section: Factors Affecting Vaginal Microbial Ecologiesmentioning
confidence: 99%
“…More than 200 sexually transmitted pathogens have been reported in animals covering a wide phylogenetic range (Lockhart, Thrall, & Antonovics, 1996). It has been suggested that menstruation evolved to protect against sperm-borne pathogens (Profet, 1993;Sobo, 1994). While it seems more likely that menstruation evolved in association with gestation rather than as a pathogenprotection mechanism (Finn, 1998;Strassmann, 1996), sexual intercourse as an avenue for disease transmission is undeniable and likely influenced the evolution of reproductive behavior.…”
Section: The Risk Of Sexmentioning
confidence: 99%
“…According to Profet (1993), in mammals the spermatozoa themselves are the vectors for pathogens, rather than the seminal fluid; in women, estrus is the period during which defense against pathogens is highest, thus inhibiting coital transmission. Mucosal immunity as a surface protection system (Brandtzaeg et al 1999) against genital tract parasitic flagellates deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Flagellates, bacteria, and viruses have been found in menstrual blood, semen, and vaginal fluid, and also adhering to spermatozoa (Smith & Dobson 1992, Profet 1993, Silverman et al 1994). Blood flagellates of the genera Leishmania and Trypanosoma have been observed in urine, macrophages of genital mucosa, semen, and the mucous exudate of the penis (Symmers 1960, Hoare 1972, Uche & Jones 1992, Mebrahtu et al 1993).…”
mentioning
confidence: 99%